Evaluation of the efficacy of a web-based work-related asthma educational tool. (25th November 2016) - Lipszyc, Joshua C.; Gotzev, Simeon; Scarborough, Jack; Liss, Gary M.; Gupta, Samir; Tarlo, Susan M.
Abstract: Background : Work-related asthma (WRA) has been estimated to account for 15–20% of adult asthma cases. Studies have indicated that a substantial number of asthma patients have inadequate knowledge of work-related effects on their disease, which may contribute to suboptimal asthma control. A Canadian web-based educational tool on WRA was developed to address this knowledge gap in the population. Objective : To evaluate the effectiveness of this web-based tool. Methods : Participants were recruited prior to a routine visit at a tertiary care asthma clinic in Toronto. A brief WRA knowledge questionnaire was developed and administered immediately before and after using of the web-based educational tool, and one year later. Results : The study sample ( N = 34) was mostly female (68%) with a mean age of 50.7 (SD, 17.2). Participants demonstrated significant improvement in questionnaire scores following interaction with the tool. The mean score increased from 76% (SEM = 2.1) to 84% (SEM = 1.7) ( p = 0.001). On average, scores improved on 12 of the 13 questionnaire items. A 1-year follow-up of a sample of 19 participants demonstrated a slight reduction in mean scores, from 86% (SEM = 1.9) to 84% (SEM = 1.9), but still demonstrated a trend towards a higher score than the baseline (78%; SEM = 2.9; p = 0.08). Conclusions : Our findings suggest that the educational tool has a positive effect on WRA knowledge, and that knowledge may be retained long-term. Future studies are needed in non-tertiary care clinic populations which may possess less baseline knowledge of WRA.